A study on marine industry and environment of China: regarding Japan's experience. Issue 1 (2nd January 2019) - Dou, Qun; Zhang, Zhenya
ABSTRACT: China is facing the challenge of many marine environment problems with rapid economic growth. Japan had experienced similar marine environmental pressure during its industrialization and had been facing the problem through successful environment policy step by step. The paper reviews the lessons and experiences of Japan's marine environment protection and analyzes the marine environment pollution in China and its causes, taking Shandong province as a case, such as GDP-oriented economic growth, heavy coal assumption, etc. The paper also analyzes the marine industry with focuses on coastal tourism and its relationship with marine environment. Suggestions on polices are provided based on the analysis on China' marine environment and Japan's experience.